Evaluation of an educational video about home bathing of newborns: a methodological study with parents and caregivers - Fernanda Garcia Bezerra Góes; Iasmym Alves de Andrade Soares; Aline Cerqueira Santos S. Silva; Ana Carla Silveira de Sá; Brenda Lucas Campos; Liliane Faria da Silva; Laura Johanson da Silva (Universidade Federal de Goias, 2024)
Objective: to evaluate the educational technology in video format about the bath of newborns at home according to their parents/caregivers' perceptions. Methods: a methodological study was conducted in a maternity hospital in the state of Rio de Janeiro, Brazil. Twenty parents/caregivers participated in the assessment of a YouTube video using a mobile device, and then filled out an evaluative instrument containing 26 items. Concordance indexes with a score equal to or greater than 0.8 (80.0%) were considered valid. Results: the overall average concordance index was 0.99 (99.0%). Among the evaluative items, scores ranged from 0.90 (90.0%) to 1.0 (100%), indicating an excellent assessment by family members. Conclusions: the evaluation of the video by the parents/caregivers was satisfactory, which makes it a promising instrument to be used during health education on newborn baths at home.